KEKUATAN HUKUM TERHADAP KESEPAKATAN DAMAI DALAM PERKARA KEKERASAN DALAM RUMAH TANGGA (KDRT) DITINJAU DARI PERSPEKTIF HUKUM PIDANA DAN HUKUM ISLAM DI INDONESIA - Imron Imron (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2017)
This study was conducted to answer two things : first, how enforceable peace agreement in the settlement of domestic violence (domestic violence) were evaluated from the Perspective of Criminal Law and Islamic Law in Indonesia. Second, how problems of law enforcement domestic violence (domestic violence) in Indonesia.Based on the study results showed that the force of law a peace agreement in the settlement of domestic violence from the perspective of criminal law is very strong and fundamental. In addition, the completion of domestic violence cases are resolved through a peace agreement in line with the principles and characteristics of Islamic Criminal Law the Law of Islam put the obligation of rights, charity, and the reward for anyone who can reconcile a family who face problems in the family. This also applies to the husband and wife that is in conflict within the family so as to provide awareness for both of them not to do anything that could harm the family unit itself. The purpose of law in general is to uphold justice by the creator of human volition so as to materialize the public order and peace, and purpose of Islamic law contained in the Qur'an and Al-Hadith, which is for the happiness of human life in this world and the Hereafter, by taking all that is useful and to prevent and reject all that is not useful to human life both physical and spiritual individuals and communities that preserve religion, life, intellect, lineage and property.Problems of law enforcement domestic violence in Indonesia, that cases of domestic violence have occurred which have been addressed and has been decided by the Court which has been run by law enforcement for justice and for the creation of a sense of justice that has to judge and give a verdict / impose imprisonment for offenders who have declared legally proven guilty of committing the crime of domestic violence as a form of guarantee of security to prevent domestic violence later, it still does not have a sense of justice, because they pose an ongoing problem for the victims that the victims were mostly divorced from domestic violence perpetrators and at the which eventually became a victim not only on the wife alone but also on children and the integrity of the household. So that penal mediation was the best solution to overcome the problem of domestic violence and law enforcement is the advice in the implementation of Islamic law in Indonesia.